Plasma Functionalized CNT/Cyanate Ester Nanocomposites for Aerospace Structural Applications. Issue 39 (19th October 2022) - John, Varsha Lisa; Gomathi, N.; Joseph, K.; Mathew, Dona; Chandran, Satheesh M; Neogi, S.
Abstract: Atmospheric pressure (AP) plasma treatment, a proven direct and dry means of surface modification, was deployed for the functionalization of carbon nanotube (CNT). AP plasma treatment successfully incorporated the functional groups such as −COOH and ‐NH2 onto the surface of CNT without affecting its crystallinity. Reduction in tube diameter and increased purity through the removal of amorphous carbon were confirmed by transmission electron microscopy (TEM) and Raman analysis. As a result of these surface chemistry and morphological changes induced by AP plasma treatment, the modified CNT‐cyanate ester nanocomposite exhibited enhanced dispersion via reduced van‐der Walls interaction. At optimum concentration of 0.1 wt% loading, the functionalized CNT with its high aspect ratio showed a well wetting behavior with cyanate ester (BADCy) matrix leading to remarkable increase in the mechanical properties like tensile, impact and flexural strengths and thus rendering them for potential aerospace structural applications. Abstract : Multiwall carbon nanotube was treated with atmospheric pressure nitrogen plasma to incorporate nitrogen‐containing groups. Plasma‐treated MWCNT was subsequently used as a filler material to prepare MWCNT‐t/BDACy nanocomposite. The high aspect ratio of CNT, along with the functional groups attached, helps to enhance the dispersion in the BADCy matrix. Their well‐wetting behaviour improves the mechanical properties of the composites.